(untitled) (Journal of Bio-Science, 2018)
Medicinal plant extract has long been used successfully in ‘unani’ or ‘ayurvedic’ medicine. Medicinal plant extract contains bioactive molecules and activity of these molecules may help to mitigate, eradicate or cure diseases. In the advent for the search for new medicinally important bioactive molecule, the current paper deals with the anti-oxidative, cytotoxic and phytochemical analysis of Scoparia dulcis leaf and root, Curculigo orchioides root, Pandanus fascicularis root and Baccaurea sapida leaf extract. Aqueous and methanolic extracts were made for each of the extracts where they posses significant antioxidative properties. High activities were seen in P. fascicularis and S. dulcis plant extract where IC50 values were 21.87 μg/ml and 173.36 μg/ml respectively. In toxicity test, only P. fascicularis extracts showed lethality in a dose-dependent manner where the LD50 value was 25.64 μg/ml. By the phytochemical analysis, it was found that each of these plant species possesses glycosides, protein, carbohydrates, alkaloid, flavonoid etc. which are pharmacologically active biomolecules. These important properties of those plants showed an indication that these plants can further be tested for the utilization in therapeutic purpose or in cosmetic industry. J. bio-sci. 25: 27-37, 2017